2014
DOI: 10.1016/j.smim.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune system and tissue regeneration in planarians: An area ripe for exploration

Abstract: The immune system has been implicated as an important modulator of tissue regeneration. However, the mechanisms driving injury-induced immune response and tissue repair remain poorly understood. For over 200 years, planarians have been a classical model for studies on tissue regeneration, but the planarian immune system and its potential role in repair is largely unknown. We found through comparative genomic analysis and data mining that planarians contain many potential homologs of the innate immune system th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 110 publications
1
48
0
Order By: Relevance
“…As a platyhelminthes, inside the planarian there must be a mechanism which prevent and defend the invasion and infection of pathogens. However, the planarian immune system is still largely unknown [ 44 ]. We selected genes in 15 KEGG immune-related pathways firstly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a platyhelminthes, inside the planarian there must be a mechanism which prevent and defend the invasion and infection of pathogens. However, the planarian immune system is still largely unknown [ 44 ]. We selected genes in 15 KEGG immune-related pathways firstly.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent results of candidate genes expression changes after bacteria stimulation further evidence that these genes involve in the response to bacterial infection ( S10 File ). Reports revealed that TRAF6, TRAF3 and P38 play a pivotal role in the RIG-I-like receptor signaling pathway [ 44 , 46 , 47 ]. Previously study showed that CgTRAF3 responds to bacterial and viral stimulation [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Planarians are flatworms (Platyhelminthes) with high rates of cellular turnover and an extraordinary capacity to regenerate, both processes of which are based on adult stem cells (SCs) called neoblasts (Aboobaker, 2011;King and Newmark, 2012;Pellettieri and Sanchez Alvarado, 2007;Reddien and Sánchez Alvarado, 2004;Wagner et al, 2011). The immune system of planaria has a high-degree of evolutionary conservation to the innate immune system of humans (Abnave and Ghigo, 2018;Li et al, 2018;Lu et al, 2017;Maciel and Oviedo, 2018;Peiris et al, 2014;Tsoumtsa et al, 2018). Additionally, similar to humans, planarians are able to distinguish between commensal and pathogenic bacteria (Abnave et al, 2014;Arnold et al, 2016;Keating https://doi.org/10.1016Keating https://doi.org/10.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that the immune system and inflammation are linked with cancer, but recently more and more research also illustrates the importance of the immune system in the regeneration process [174][175][176][177][178]. Cells of the immune system remove damaged cells and cell debris, produce signalling and growth factors, regulate angiogenesis and modulate the extracellular matrix environment in the first stages after injury.…”
Section: Mechanismsmentioning
confidence: 99%